Contextual Teaching and Learning Model with Learning Motivation on Poetry Writing Skills - Rentiga Asa, Shodia; Amril Amir (Journal of Education Reseach and Evaluation, 2025)
This research stems from the problem of learning poetry writing skills that still focus on completing tasks sourced from books. The dominance of the teacher's role in learning also results in a lack of opportunities for students to actively participate. In addition, limited vocabulary mastery also makes it difficult for students to develop ideas and imagination in writing poetry. This study aims to examine the effect of Contextual Teaching and Learning (CTL) learning model on poetry writing skills in students with high and low learning motivation. Furthermore, this study seeks to examine the interaction between CTL learning model and learning motivation in influencing poetry writing skills. This research used experimental method with 2x2 factorial design. Applying performance test instruments and questionnaires, this study involved 71 samples divided into an experimental group of 35 students and a control group of 36 students. Through t-test and 2-way ANOVA, this study showed that the CTL model had a significant effect on poetry writing skills, both for students with high and low learning motivation. However, the interaction between the CTL model and learning motivation did not occur significantly, meaning that the CTL learning model provides a consistent influence on poetry writing skills, regardless of the level of student learning motivation. Thus, teachers can apply the CTL model evenly and focus on applying contextual learning strategies that are relevant to students' experiences, thus helping students more easily develop their poetry writing skills.